Características genômicas da Leptospira interrogans sorovar Hardjo str. Norma: genoma do local de recombinação potencial representado pela genômica comparativa - Cosate, M. R. V.; Moreira, E. C.; Ortega, J. M.; Leite, R. C.; Haddad, J. P.; Mendes, T. A. O. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
Leptospirosis is caused by pathogenic spirochetes of the genus Leptospira spp. with worldwide distribution. In livestock, Leptospira interrogans serogroup Sejroe serovar Hardjo remain the major cause of reproductive diseases. The publication of whole genome sequence of the first Brazilian clinical isolate classified as Leptospira interrogans serogroup Sejroe serovar Hardjo str. Norma enable now to evaluate genomic features and evolution of this serovar and serogroup.